Refined risk assessment regarding certain maximum residue levels (MRLs) of concern for the active substance chlorpyrifos - European Food Safety Authority (EFSA) (EFSA Journal, 2015)
Abstract In compliance with Article 43 of Regulation (EC) No 396/2005, the European Food Safety Authority (EFSA) received from the European Commission (EC) a mandate to provide its reasoned opinion on the existing maximum residue levels (MRLs) for chlorpyrifos which might lead to consumers intake concerns on the basis of the new toxicological reference values and of the data currently available to EFSA. In order to identify the potential MRLs of concern that require a more detailed assessment, EFSA performed a first unrealistically conservative intake calculation on the basis of the existing EU MRLs for chlorpyrifos. Those potential MRLs of concern were assessed in more detail by EFSA and where the safety of the existing EU MRLs could not be confirmed by the available data, possible measures for risk mitigation were assessed by EFSA.